2014
DOI: 10.1111/sjop.12117
|View full text |Cite
|
Sign up to set email alerts
|

An atypical anxious‐impulsive pattern of social anxiety disorder in an adult clinical population

Abstract: An atypical subgroup of Social Anxiety Disorder (SAD) with impulsive rather than inhibited traits has recently been reported. The current study examined whether such an atypical subgroup could be identified in a clinical population of 84 adults with SAD. The temperament dimensions harm avoidance and novelty seeking of the Temperament and Character Inventory, and the Liebowitz Social Anxiety Scale were used in cluster analyses. The identified clusters were compared on depressive symptoms, the character dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 25 publications
5
32
1
Order By: Relevance
“…This atypical group also displayed increased functional impairment, lower education and income, and more psychiatric comorbidities. Mörtberg et al also identified these two subgroups in 84 SAD adults, finding that 24% of patients displayed anxious-impulsive traits, and additionally showed that this atypical group had low self-directedness and high levels of depressive symptoms [68]. This anxious-impulsive personality has also been shown to be elevated in stimulant-dependent individuals and their nonaffected siblings, thus supporting this trait as a risk factor for drug abuse [69].…”
Section: The Addition Of Impulsivity In Anxiety Disorders and Subsequmentioning
confidence: 94%
“…This atypical group also displayed increased functional impairment, lower education and income, and more psychiatric comorbidities. Mörtberg et al also identified these two subgroups in 84 SAD adults, finding that 24% of patients displayed anxious-impulsive traits, and additionally showed that this atypical group had low self-directedness and high levels of depressive symptoms [68]. This anxious-impulsive personality has also been shown to be elevated in stimulant-dependent individuals and their nonaffected siblings, thus supporting this trait as a risk factor for drug abuse [69].…”
Section: The Addition Of Impulsivity In Anxiety Disorders and Subsequmentioning
confidence: 94%
“…It seems that impulsivity and anxiety sensitivity have a complex function in SAD. However, according to our knowledge, there is no study in the literature that examined the relationships between these two characteristics and severity of SAD concurrently (6)(7)(8)(9)(10)(11)(12)(16)(17)(18). Thus, the aim of this study is to investigate impulsivity and anxiety sensitivity characteristics in SAD patients and to investigate the relationships between these characteristics and the severity of SAD symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Past research has shown that most of the psychiatric disorders including anxiety disorders, mood disorders, and Attention Deficit and Hyperactivity Disorder (ADHD) may have some impulsivity characteristics, which make treatment and progress of the disorders poorer than those, which do not have impulsivity characteristics (13)(14)(15). Some studies in the literature also have shown that some subgroups of patients with SAD can display impulsive behaviors instead of the avoidance behaviors that we often expect to observe in patients with SAD (16)(17)(18). Kashdan et al examined the behavior patterns and socio-demographic characteristics of a sample of 1,832 individuals in their study and, found that 79% of the SAD samples exhibited typical behavioral patterns such as behavioral inhibition and submission, whereas 21% of displayed more anger and impulsivity characteristics than individuals with typical behaviors (16).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations